Enhanced expression of thioredoxin-interacting-protein regulates oxidative DNA damage and aging - Oberacker, Tina; Bajorat, Jörg; Ziola, Sabine; Schroeder, Anne; Röth, Daniel; Kastl, Lena; Edgar, Bruce A.; Wagner, Wolfgang; Gülow, Karsten; Krammer, Peter H. (FEBS letters, 2018)
The “free radical theory of aging” suggests that reactive oxygen species (ROS) are responsible for age-related loss of cellular functions and, therefore, represent the main cause of aging. Redox regulation by thioredoxin-1 (TRX) plays a crucial role in responses to oxidative stress. We show that thioredoxin-interacting protein (TXNIP), a negative regulator of TRX, plays a major role in maintaining the redox status and, thereby, influences aging processes. This role of TXNIP is conserved from flies to humans. Age-dependent upregulation of TXNIP results in decreased stress resistance to oxidative challenge in primary human cells and in Drosophila. Experimental overexpression of TXNIP in flies shortens lifespan due to elevated oxidative DNA damage, whereas downregulation of TXNIP enhances oxidative stress resistance and extends lifespan.
Gesehen am 25.03.2020